A Usability Testing of a Higher Education Mobile Application Among Postgraduate and Undergraduate Students - Nik Ahmad, Nik Azlina; Hussaini, Muhammad (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The advancement in technology has produced innovative applications for educational purpose. Numerous higher education applications have aroused in recent years. Therefore, it is essential to strive for a high usability application. This study presents a usability evaluation of a higher education mobile application in Universiti Kuala Lumpur. The study was conducted using usability testing methodology to measure three usability factors which are effectiveness, efficiency and satisfaction. A number of 64 participants from postgraduate and undergraduate programme were subjectively selected. The result reveals that the application is effective, efficient and meet the users’ satisfaction on its usability, with the satisfaction rate of 82.15%. Several issues with regard to the application were highlighted by the respondents during the usability test. Therefore, despite of positive results, several recommendations with regards to improve the usability of the application were proposed in this study.